EVALUATING THE IMPACT OF THE “PROJECT-BASED LEARNING WITH ETWINNING/ERASMUS+ FOR INTERCULTURALITY” COURSE ON INTERCULTURAL AND DIGITAL COMPETENCES - Кшевецький, Володимир Сергійович (Харківський національний педагогічний університет імені Г. С. Сковороди, 2025)
The research evaluates the impact of the blended-learning course “Project- Based Learning with eTwinning/Erasmus+ for Interculturality,” offered collaboratively by Stuttgart University, Pädagogische Hochschule Ludwigsburg, and Hohenheim University during the 2025 summer semester. This 13-week course, facilitated via Zoom, Moodle, and eTwinning’s TwinSpace, aimed to enhance participants' skills in project-based learning, educational project management, and international collaboration. Data was gathered through post- course self-assessment surveys combining quantitative Likert-scale responses and qualitative open-ended feedback from 20 participants.
Keywords: Project- Based Learning, eTwinning, Erasmus+, Interculturality